2003
DOI: 10.1200/jco.2003.08.101
|View full text |Cite
|
Sign up to set email alerts
|

High Prognostic Value of p16INK4 Alterations in Gastrointestinal Stromal Tumors

Abstract: We believe that the evaluation of p16INK4 alteration status is a helpful prognosticator, particularly in the benign and borderline groups of GISTs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
92
4
10

Year Published

2004
2004
2015
2015

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 142 publications
(113 citation statements)
references
References 30 publications
7
92
4
10
Order By: Relevance
“…This tumor occurs in both sexes equally (19,26,27) or slightly higher in men as observed in this study (8,23,32) . The primary site of tumors noted arise in the small bowel (40%) or in the stomach (32%) in contrast to others which this tumor commonly arise mostly in the stomach (60%-70%) and in the small intestine in a smaller frequency (26%-35%) (29) .…”
Section: Discussionsupporting
confidence: 71%
See 1 more Smart Citation
“…This tumor occurs in both sexes equally (19,26,27) or slightly higher in men as observed in this study (8,23,32) . The primary site of tumors noted arise in the small bowel (40%) or in the stomach (32%) in contrast to others which this tumor commonly arise mostly in the stomach (60%-70%) and in the small intestine in a smaller frequency (26%-35%) (29) .…”
Section: Discussionsupporting
confidence: 71%
“…This antigen provides information about the proportion of active cells in the cell cycle (15,29,32,35,37) .…”
Section: Introductionmentioning
confidence: 99%
“…Alterations of the G1/S-phase transition inhibitor p16 INK4A , which are frequently observed in high-risk/malignant GISTs, may contribute to this difference. 22,23 These findings are in line with our previous observation that the presence of epithelioid/mixed components in GISTs with biphasic pattern was associated with higher mitotic activity, higher expression of Ki67 and higher number of chromosomal copy number changes compared with the spindled component in the same tumor. 16 In that study, our observations suggested a clonal progression through sequential chromosomal alterations, with a shift in the histomorphological growth pattern from spindled to epithelioid/mixed phenotype.…”
Section: Discussionsupporting
confidence: 91%
“…Schneider-Stock et al 31 reported that p16 INK4A alteration was detected in benign, borderline and malignant GISTs but nevertheless was considered as an independent poor prognostic factor. The apparent discrepancy with our findings may relate to the difference in classification methods.…”
Section: Discussionmentioning
confidence: 99%